SUSTAINABLE DEVELOPMENT AND TOURISM OF URBAN HERITAGE: AN IMPERATIVE FOR THE FUTURE. CASE OF DACHRA HAMRA IN EL KANTARA, BISKRA, ALGERIA - Souad Belhannachi; Meriem Benmechiche; Imene Bensid; Oualid Meddour (International Journal of Innovative Technologies in Social Science, 2024)
In Algeria, as in the rest of the world, urban heritage, specifically historical centers, attracts many visitors due to their heritage significance. However, the growth of tourist flows and the attractiveness of these cities are dependent on the conservation, enhancement, and sustainable preservation of this heritage. The original core of the city of El Kantara in Biskra, Algeria, Dachra El Hamra, remains inhabited and is distinguished by its unique architecture and urban organization. This village is regarded as a cultural model of great value. From a tourist perspective, Dachra El Hamra holds particular interest as both tangible and intangible heritage. This interest is heightened by its integration within lush landscapes, characterized by date palm orchards thriving at the foot of its majestic cliffs and impressive gorges. The village of Dachra El Hamra remains at the center of concerns for local authorities and communities. The objective of this study revolves around this urban heritage, considering the criteria of sustainable development while promoting local and international tourism. To achieve this, we developed an evaluation using the RST02 grid, supplemented by a direct questionnaire conducted with the stakeholders involved in its management.